Assessment of Critical Thinking Ability in Science Learning Using Watson-Glaser Critical Thinking Appraisal (WGCTA) - Rifda Nur Hikmahwati Arif (ARRUS Journal of Social Sciences and Humanities, 2024)
Students must have critical thinking skills in order to be able to face various personal and social problems in their lives. Critical thinking ability is the ability to think reflectively and reason in making decisions. This research is a qualitative descriptive study with the aim of designing an assessment of critical thinking skills in accordance with the concept of the critical thinking test model developed by Watson and Glaser with the title Watson-Glaser Critical Thinking Appraisal (WGCTA). In this article there are 5 indicators discussed in science learning, namely indicators: Drawing Conclusions (Inference), Assumptions (Recognizing Assumptions), Deduction (Deduction), Interpreting Information (Interpretation), Analyzing Arguments (Evaluation Argument).